SEMIOTIC VERBAL AND VISUAL SIGN FOUND IN KUTA FIVE STAR HOTELS ADVERTISEMENTS - Karminova Anggela; Ni Wayan Suastini; I Wayan Juniartha (ID Solutions, 2022)
This study concerned on finding out the messages carried by both verbal and nonverbal signs in Kuta five star hotel advertisements. The data were taken from internet. The data were collected by observation method. The collected data were analyzed by qualitative method using theory of semiotics from Saussure (cited in Chandler 2001), the theory of meaning by from Barthes (1967), and theory color term from Cerrato (2012). The message is presented in formal and informal way. Our findings show first, the verbal signs that appear have connotative and denotative meanings can provide meaningful messages to the reader. Second, the visual signs that appear show several images and colors that have various meanings according to the context behind the advertisement.